1982
DOI: 10.1287/opre.30.4.680
|View full text |Cite
|
Sign up to set email alerts
|

Perishable Inventory Theory: A Review

Abstract: This paper reviews the relevant literature on the problem of determining suitable ordering policies for both fixed life perishable inventory, and inventory subject to continuous exponential decay. We consider both deterministic and stochastic demand for single and multiple products. Both optimal and suboptimal order policies are discussed. In addition, a brief review of the application of these models to blood bank management is included. The review concludes with a discussion of some of the interesting open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
423
0
13

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 957 publications
(437 citation statements)
references
References 59 publications
1
423
0
13
Order By: Relevance
“…Nahmias [17] reviewed the literature on inventories in perishables, looking at perishable products with fixed lives (stochastic and deterministic demand), and random variables (with periodic review and exponential decay), as well as control rules for certain types of inventories with perishable products. The studies reviewed by Nahmias [17] revealed that a considerable number of problems on perishable products still remain unresolved; for instance, an extremely difficult problem is the continuing review for products with fixed lives and positive lead-time. Nahmias suggested that a control rule based on the expected life of the inventory at hand could be more appropriate for the perishable goods than one based on the number of items in stock.…”
Section: A Transport Logistics Of Inventories In the Food Chainmentioning
confidence: 99%
“…Nahmias [17] reviewed the literature on inventories in perishables, looking at perishable products with fixed lives (stochastic and deterministic demand), and random variables (with periodic review and exponential decay), as well as control rules for certain types of inventories with perishable products. The studies reviewed by Nahmias [17] revealed that a considerable number of problems on perishable products still remain unresolved; for instance, an extremely difficult problem is the continuing review for products with fixed lives and positive lead-time. Nahmias suggested that a control rule based on the expected life of the inventory at hand could be more appropriate for the perishable goods than one based on the number of items in stock.…”
Section: A Transport Logistics Of Inventories In the Food Chainmentioning
confidence: 99%
“…Nahmias (1982), in a comprehensive survey paper, reviews the literature on ordering policies until 1982. The model introduced by Kaspi and Perry (1983), is perhaps the ÿrst to analyze a PIS with random input.…”
Section: Analysis Of a Sampling Control Scheme For A Perishable Invenmentioning
confidence: 99%
“…Although several works cited in Nahmias (1982) (e.g., Graves (1982), Barrer (1957), Finch (1960), Daley (1965), and Takà acs (1974)) have used such an analogy, the model of Kaspi and Perry (1983) is completely di erent. They consider an inventory system for which arrival of items, as well as demands for these items are independent Poisson processes.…”
Section: Analysis Of a Sampling Control Scheme For A Perishable Invenmentioning
confidence: 99%
“…Over the last 30 years four review papers have been published on the general field (see [17] for the first review paper, [26], [12] and recently, a comprehensive updated monograph by Nahmias [18]). According to the review papers above it seems that most of the work in the field looks on the topic from an optimal control point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In this model there is no controller, since the input is random. In addition, it is noted in [11,17] that the finite shelf life of the stored items in the inventory system can be interpreted as the finite patience of the customers in a single server queueing system, also known as the finite dam model, which has been extensively studied (e.g. [4,8,9,7,3,24]).…”
Section: Introductionmentioning
confidence: 99%